Cannabis and international criminology: tolerance, aversion, and legal technical assistance - Wheeldon, Johannes (Crime, law and social change, 2024)
For decades, developing countries have faced international pressure to adopt the techniques and tactics consistent with the drug war. These have had profound and adverse consequences. While cannabis prohibition and drug control generally are topics that lend themselves to established comparative studies, engaging cannabis as a substantive topic engages numerous aspects of criminal justice systems. In this paper, we link cannabis to concepts related to recent formulations of international criminology. Next, we outline how the history of cannabis prohibition requires adopting a more critical global lens and consider the role of legal technical assistance to support countries renegotiating cannabis control in the twenty-first century. Beyond the formal tools and informal techniques commonly used within legal technical assistance, we argue expanding tolerance can disrupt the tendency for reform to expand social control. While embracing tolerance may serve as an antidote to some penal modalities, this must be combined with policies that regulate the aversion many feel toward cannabis and people who use it. Harm reduction provides a useful frame to combine these concepts and orient critical models of international criminology.